George Orwell and Totalitarianism: A Master of Political and Social Commentary - Gurung, Gol Man (Interdisciplinary Journal of Management and Social Sciences, 2024)
This analysis delves into George Orwell's legacy as a British writer and journalist, focusing on his incisive scrutiny and critique of political and social structures, with a specific emphasis on totalitarianism. Through a comprehensive examination of Orwell's seminal works, "Animal Farm" and "1984," the study aims to reveal the enduring relevance of his critiques by contextualizing them within the socio-political landscape of his era and drawing connections to contemporary issues of government power, surveillance, and individual liberties. Employing a multifaceted methodology encompassing literary analysis, biographical exploration, historical contextualization, comparative analysis, and the incorporation of scholarly perspectives, the research provides a nuanced understanding of Orwell's contributions, emphasizing his impact on literature, political thought, and the ongoing discourse surrounding the perils of unchecked authority. In conclusion, Orwell's enduring legacy emerges as a critical observer and commentator, whose works remain powerful reflections on totalitarianism, surveillance, and the fragility of individual freedoms, resonating globally as relevant and cautionary narratives.